Strategic Revitalization of Cultural Landscapes through Heritage Tourism: A Case Study of Desa Sibandang, North Tapanuli Regency: English - Simanungkalit, Theodora M; Dwi Lindarto; Revida, Erika; Charloq (Asian Multidisciplinary Research Journal of Economy and Learning, 2025)
Desa Sibandang, situated along the eastern edge of Lake Toba in North Tapanuli, Indonesia, possesses rich cultural and historical assets, including traditional Batak architecture, ceremonial stone structures, and intangible heritage such as ulos weaving. Despite being designated part of the Lake Toba Super Priority Tourism Destination (DPSP), the village has yet to realize its full potential as a sustainable heritage tourism destination. This study explores strategic revitalization opportunities by identifying internal strengths, weaknesses, and external environmental dynamics through a qualitative descriptive approach. Data were collected via 15 semi-structured interviews, field observations, and analysis of planning and policy documents. The study employed a SWOT (Strengths, Weaknesses, Opportunities, Threats) analysis followed by a TOWS matrix to formulate actionable strategies. Findings indicate a favorable internal environment (IFE score: 2.92) and a strong external opportunity landscape (EFE score: 3.02), supporting an aggressive development strategy. Key challenges include inadequate infrastructure, weak tourism governance, and limited community capacity. Strategic directions proposed include digital heritage promotion, infrastructure enhancement, cultural interpretation training, and inclusive local governance mechanisms. This research contributes to heritage tourism planning by offering a replicable framework for integrating cultural preservation with community-based tourism development. It also emphasizes the importance of ethical, participatory planning in safeguarding the cultural integrity of heritage-rich rural villages.